Gadus morhua - Gates, AR (Hurricane Energy, 2016)
The cod was feeding on crustaceans in the water column. A cod appeared as we examined the sponge with the ROV's video and stills camera. It was catching small crustaceans that were attracted to the vehicle's lights. The sponge resembles Mycale sp. Also note the numerous ophiuroids (brittle stars) on the sponge and the galatheid (squat lobster) in the foreground.